INVENTORY ANALYSIS OF SOYBEAN RAW MATERIALS USING ECONOMIC ORDER QUANTITY METHOD (CASE STUDY: CANGKIANG TOFU FACTORY, AGAM REGENCY) - Eli Febriani; Rayzul Hawari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The purpose of this study is to find out how to manage the inventory of soybean raw materials using the economic order quantity method at the Tofu Shell factory, Agam Regency. The method used in this study is a qualitative approach. There were 4 informants for this research including factory owners, managers and 2 other employees in each production. Data collection techniques by conducting in-depth interviews, observations are then analyzed in the form of three stages, namely data reduction, data presentation and verification / drawing conclusions. From the results of research conducted at the Tofu Cangkiang Factory, Agam Regency shows that the Tofu Cangkiang factory still uses the method of thinking in purchasing raw materials, the Tofu Shell factory is good at using the EOQ (economic order quantity) method so that the Tofu Shell factory can find out the optimal inventory of raw materials and can save costs incurred when purchasing raw materials. The Tofu Shell factory has implemented sharia business principles, namely by maintaining consumer satisfaction by increasing trust and honesty, transparency in explaining product quality and prices to consumers, competing fairly and being fair to its employees.